TESTING THE EFFECTS OF PRESENCE URANIUM IN DRINKING WATER FROM INDIVIDUAL WELLS IN VILLAGE DUBRAVICA IN BRANIČEVO DISTRICT ON PUBLIC HEALTH - Rajković, Miloš Budimir (Journal of Agricultural Sciences (Belgrade), 2021)
Village Dubravica is partially located over the western lignite deposits Kostolac basin. The examination of dry residue obtained from drinking water from two individual wells by radiographdiffraction analysis, based on typical peak, it was fortified the presence of uranium in drinking water. Indirect method by Rajković and associates reliably proven that in the I sample concentration of uranium in drinking water is 1.86 times higher and that the concentration of uranium – II sample only 22% lower than the Maximum Allowable Concentration values required by the Regulations. Analysis of the result of the introduction of uranium in the human body showed that in this way brings 0.84 to 2 mg of uranium in the human organism per annum, or 0.09 to 0.22 mg deposited annually in the kidney. Assessment of the potential health risk due to the presence of uranium in drinking water indicated that the population using drinking water from wells and in a short time interval threatened by uranium. As for the long-term risk, the budget noted that in the case of I sample of drinking water affects about 25, and in the case of II sample of drinking water 10 inhabitants from 1000 inhabitants. As the main target of the attack of uranium in the human body is kidney, a fact easily and long-term weakening of the kidneys can be so that as many as 75% of the functions kidneys destroyed in order to see the first clinical symptoms. This phenomenon is observed among the population along the river Kolubara, Drina, Sava and Morava and is called Endemic Nephropathy. As possible causes emphasize the elements that are found in trace amounts (Pb, Cd, Si), live agents (bacteria and viruses), fungal plant toxins, genetic factors and immune mechanism, but not the uranium in the water for drinking. The tests, performed in this study clearly show in the role of uranium in the epidemic, endemic nephropathy, which is growing and which do not have acute phase of the disease, but already progressed to renal failure and end-stage kidney disease. Official datas speaking of the rise of endemic nephropathy and diabetes and increasing their share in diseases, as well as overall mortality rates, which amounts to 18.19%, clearly indicate that the role of uranium in the environment Braničevo district in any way should not be ignored. Because of the terrain on which there are settlements must be monitored uranium and its migration through the environment, for the movement of which there are, unfortunately, all the conditions.